Ecuador : 2016 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation discusses that declining oil prices, US dollar appreciation, and limited access to international financing have worsened the fiscal, economic, and financial outlook. The focus of discussions was that despite the weak prospects there are still downside risks in the event that oil prices fall again, external financing becomes even more constrained, or confidence in the economy and the banking system begins to weaken. In the financial system, the main concern resides in a short-term risk of liquidity shortfalls, but credit quality concerns dominate over the medium term. The authorities' policy response to the imbalances has been timely but still insufficient given the size of the shocks, the urgent nature of the vulnerabilities, and reduced foreign currency reserves. Real GDP is expected to contract significantly this year and next. In order to prevent liquidity risks in the financial system, the authorities should limit recourse to domestic financing and, as necessary, assist in a timely way banks that develop liquidity or capital shortfalls, as well as enhance crisis preparedness and contingency planning.